2008
DOI: 10.1177/0027950108099841
|View full text |Cite
|
Sign up to set email alerts
|

Could Early Warning Systems Have Helped To Predict the Sub-Prime Crisis?

Abstract: Abstract:One of the features of the sub-prime crisis, that began in August 2007, was its unexpected nature. It came as a surprise not only to most financial market participants but also in some degree to the policy community. In this context, we seek to assess whether early warning systems based on the logit and binomial tree approaches on the UK and US economies could have helped to warn about the crisis. We also consider a "check list approach" of indicators based on history. Although not all of the compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 10 publications
(18 reference statements)
2
49
0
6
Order By: Relevance
“…There is a large literature on systemic banking crisis prediction via so called early warning systems (EWSs) which utilise a range of estimators from panel logit (as in Demirguc-Kunt andDetragiache 2005, Davis andKarim 2008a) to signal extraction (Kaminsky and Reinhart 1999, Borio and Lowe 2002, Borio and Drehmann 2009) to binary recursive trees (Duttagupta and Cashin 2008, Karim 2008, Davis and Karim 2008b.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large literature on systemic banking crisis prediction via so called early warning systems (EWSs) which utilise a range of estimators from panel logit (as in Demirguc-Kunt andDetragiache 2005, Davis andKarim 2008a) to signal extraction (Kaminsky and Reinhart 1999, Borio and Lowe 2002, Borio and Drehmann 2009) to binary recursive trees (Duttagupta and Cashin 2008, Karim 2008, Davis and Karim 2008b.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of recent attempts to integrate the two approaches to analyze interaction effects of macro-financial variables through, for example, the use of the binary classification tree technique (Duttagupta and Cashin, 2008;Davis and Karim, 2008b), the literature suggests that the empirical strategy based on the estimation of the binomial multivariate logit outperforms the signals approach. Demirgüç-Kunt and Detragiache (2000), Davis and Karim (2008a;2008b) and Alessi et al, (2015) show that crisis probabilities estimated through the binomial multivariate logit exhibit lower type I (missed crises) and type II (false alarms) errors than the signals approach and therefore provide a more accurate basis for building an EWS.…”
mentioning
confidence: 99%
“…Demirgüç-Kunt and Detragiache (2000), Davis and Karim (2008a;2008b) and Alessi et al, (2015) show that crisis probabilities estimated through the binomial multivariate logit exhibit lower type I (missed crises) and type II (false alarms) errors than the signals approach and therefore provide a more accurate basis for building an EWS.…”
mentioning
confidence: 99%
“…They showed that they outperform traditional variables such as GDP growth, inflation and real interest rates. Davis and Karim (2008) used logit and binomial tree approaches that have been successful in predicting banking crises (Karim (2008)). Overall, the different early warning systems were just partially helpful to predict the subprime crisis.…”
Section: Financial Market Stability and Early Warning Systems For Finmentioning
confidence: 99%